1997
DOI: 10.1021/om9703090
|View full text |Cite
|
Sign up to set email alerts
|

Stereoregular Polymerization of Phenylacetylenes Catalyzed by [Hydridotris(pyrazolyl)borato]rhodium(I) Complexes

Abstract: Rhodium(I) tris(pyrazolyl)borate complexes TpR2Rh(cod) (R = Me, Ph, i-Pr) were found to serve as efficient catalysts for highly stereoregular polymerization of phenylacetylene derivatives (p-YC6H4C⋮CH; Y = H, Me, Cl, CN, CO2Me, COMe, NO2) to give poly(phenylacetylene) species having a head-to-tail, cis-transoidal structure. The catalytic activity was strongly affected by the substituents (R) at the 3- and 5-positions of the pyrazolyl groups, and the more sterically demanding R groups led to higher catalytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

4
50
0

Year Published

1999
1999
2004
2004

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 30 publications
4
50
0
Order By: Relevance
“…The activity of 5 in polymeristo be essential for its catalytic activity in the polymerisation ation of phenylacetylene also reflects the occurrence of of phenylacetylene. [9] In accordance with this we observed κ 2 Ϫκ 3 isomerism. L Bzl Ϫ in 6, the Ir-analogue of 5, shows that rhodium complex 5, but not iridium complex 6, is an no sign of pyramidal inversion of N Bzl amine via κ 2 Ϫκ 3 isomactive catalyst for the polymerisation of phenylacetylene erism in solution, and is tridentate in the solid state.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…The activity of 5 in polymeristo be essential for its catalytic activity in the polymerisation ation of phenylacetylene also reflects the occurrence of of phenylacetylene. [9] In accordance with this we observed κ 2 Ϫκ 3 isomerism. L Bzl Ϫ in 6, the Ir-analogue of 5, shows that rhodium complex 5, but not iridium complex 6, is an no sign of pyramidal inversion of N Bzl amine via κ 2 Ϫκ 3 isomactive catalyst for the polymerisation of phenylacetylene erism in solution, and is tridentate in the solid state.…”
supporting
confidence: 87%
“…The mo-coordination of N Py , and thus results in five coordination. lecular mass (M n ) and the high stereoregularity (head-totail cis-transoidal structure) of the obtained poly(phenylacetylene) are similar to those of poly(phenylacetylene) pre-Experimental Section pared with (Tp R2 )Rh I (cod) [9] and other rhodium cataGeneral Methods: All reactions were performed under a nitrogen lysts.…”
mentioning
confidence: 83%
“…12 We have found that ionic liquids, as well as ammonium salts, are efficient co-catalysts, especially in polymerization catalysed by RhTp(cod) (1). Very good results have also been obtained with alcohols as solvents.…”
mentioning
confidence: 94%
“…5 Rhodium(I) tris(pyrazolyl)borate complexes with homoand hetero-scorpionates, RhTp (cod), are efficient catalysts of stereoregular polymerization of phenylacetylene derivatives. 12,13 Catalytic activity has been observed only for complexes with substituents (R) in the 3-and 5-positions of the pyrazolyl ring, and the more bulky R-groups usually cause higher catalytic activity. In contrast, rhodium complexes with unsubstituted tris(pyrazolylborate) (Tp) and bis(pyrazolylborate) (Bp) ligands (RhTp(cod) (1), RhBp(cod) (2); Fig.…”
mentioning
confidence: 99%
See 1 more Smart Citation